Pan : the Great God's Modern Return - Robichaud, Paul, 1971- (Reaktion Books Ltd, 2021)
"Robichaud (English, Albertus Magnus College) offers readers an exercise in thinking through the many and varied relationships between religion and culture. His subject is Pan, that horned, lusty, and cloven hoofed god who was human and goat and deity all wrapped into one. The author begins with Pan's origins in Arcadia--in Greece's Peloponnese--where Pan was a rural god who had the capacity to induce panic with his music. The mythological god Pan died, but Pan the creature continued into medieval and modern times as a literary reappropriation of the joys of nature and depth beneath rational comprehension. Romantic poets rejoiced in the appreciation of nature, and Victorian writers sought the powers of irrational dimensions of culture and nature, as did modern poets Cummings, Ezra Pound, and Yeats. Some 20th-century novelists (Lawrence, Huxley, Faulkner) and composers (Sibelius, Debussy, Ravel, Elgar, Holst, Ralph Vaughan Williams) paid heed to Pan, as do contemporary bands Comus, Traffic, Waterboys, and Jethro Tull. Robichaud devotes the last chapter, "Contemporary Pan," to Pan's appearance in the work of Carl Jung and James Hillman, where Pan lived on in the psyche. An insightful and stimulating read!" - Choice Review